Effect of services trade liberalization in Africa - (:unkn) unknown (My University, 2008)
This thesis assesses the impact of services trade liberalization in Africa. Beyond an introductive chapter (chapter1), the thesis contains three chapters: the chapter 2 assesses the determinant of market power in telecommunications industry. The third analyses the impact of service trade on economic growth focusing on the services of telecommunications and finances. The fourth proceed to the simulation of service liberalization impact on poverty relying on the case of telecommunication in Cameroon. The chapters 2 and 3 are based on aggregated data from 30 African countries between 1997 and 2004. Relying on structural models and using the 3SLS estimates, three sets of results emerge from our empirical analysis: (i) Concerning the telecommunications, the African industry faces significant market power practices: Three policy factors seem to be affecting negatively this market power: the unilateral efforts in terms of liberalization (increasing in number of operators) as well as strengthening of sectoral regulation, and the multilateral commitments to liberalize in the framework of the GATS. However, it appears that multimarket contact of telecommunications operators is an important factor enhancing the cooperative pricing behavior. (ii) Regarding the growth effect of services liberalization, the level of competition has a strong effect on telecommunications services accessibility, which in turn influences the income growth. (iii) . In the case of financial sector, the services trade liberalization (openness) emerges to be a strong determinant of market structures, while the sectoral performances indicators (credit to private and spread) emerge as strong determinants of income growth. The chapter 4 uses the elasticities estimated in the previous chapters and adopts the micro-macro simulation approach to analyze the poverty (Shen and Ravallion, 2004). It relies on Cameroonian SAM of 2001 and Cameroonian household's data of income survey for 2001 (ECAM II).
Keywords: African Research